2015
DOI: 10.1210/jc.2014-3676
|View full text |Cite
|
Sign up to set email alerts
|

Does Contralateral Suppression at Adrenal Venous Sampling Predict Outcome Following Unilateral Adrenalectomy for Primary Aldosteronism? A Retrospective Study

Abstract: In this study, the presence of CS correlated with good BP and biochemical outcomes from surgery. This finding suggests that CS should be a factor in deciding whether to offer surgery for treatment of PA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 22 publications
7
79
5
1
Order By: Relevance
“…3,4 Confirmatory testing and synacthen test were performed as detailed elsewhere. [13][14][15] All patients included in the analysis gave written informed consent, and approval from the local ethics committees was obtained for the use of these retrospective data. The study adheres to the principles of the Declaration of Helsinki and to institutional guidelines.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Confirmatory testing and synacthen test were performed as detailed elsewhere. [13][14][15] All patients included in the analysis gave written informed consent, and approval from the local ethics committees was obtained for the use of these retrospective data. The study adheres to the principles of the Declaration of Helsinki and to institutional guidelines.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In particular, interfering medications were withdrawn at least 4 weeks prior to testing and the aldosterone to renin ratio (ARR) was used as a screening test. The diagnosis of PA was confirmed using fludrocortisone suppression testing, the intra-venous saline loading test or the captopril challenge test, as detailed elsewhere (13,14). All patients with a confirmed diagnosis of PA underwent adrenal CT scanning or MRI and AVS for subtype differentiation.…”
Section: Novelty and Significancementioning
confidence: 99%
“…In addition, AVS protocols vary among centers in the following aspects: the procedure of sampling (simultaneous or sequential bilateral sampling), the mode of stimulation (unstimulated, continuous or bolus infusion of cosyntropin), and the adoption of selectivity index (SI) and lateralization index (LI) (5, 6, 7), thus, cross comparison of the results can prove challenging. Some investigators have reported that the 'contralateral suppression index (CSI)' could be another key finding to identify the lesions responsible for excess secretion of aldosterone (6,8,9,10). In APA patients with mild-to-moderate secretion of excess aldosterone, especially in those with computed tomography (CT)-undetectable aldosteroneproducing micro-adenoma (micro-APA), some centers have reported to detect laterality of hyperaldosteronism using their own protocols (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…To directly compare the performance of eight other steroids from the adrenal gland to cortisol, we applied the previously validated criteria for catheter positioning and lateralization [7]. The contralateral suppression of aldosterone secretion, defined as lower normalized aldosterone in a nondominant adrenal gland than that of a peripheral sample, was suggested to be a predictor for biochemical resolution of PA and improvement in blood pressure [22]. Thus, it has been used as additional criteria for identifying patients with unilateral disease when cosyntropin is not given [23].…”
Section: Discussionmentioning
confidence: 99%